IMPROVING STUDENTS` COMPREHENSION ON COMMANDS THROUGH TPR COMBINE WITH REPETITION DRILL - Lina, Lina; Sofian, Sofian; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improve students comprehending on commands given. The method of this research is collaborative classroom action research.. The instruments used to collect the data are field note and individual test checklist form. The research finding of 1st cycle has shown that lack of understanding of the students in comprehending the commands is the main reason of this problem. However, the situation changes in 2nd cycle when the teacher keep repeating the commands and showing actions used as the technique to clarify the meaning of the commands which is called Total Physical Response combine with repetition drill. TPR combine with repetition drill improve students to comprehend the commands so that they will be easier to carry out the command given. In addition, the students will be more motivated to learn more due to the TPR isanÂ  attractive technique for students.Â Keywords : Total Physical Response, Repetition drill, Commands, Classroom Action Research.Â